Reevaluation of the largest published morphological data matrix for phylogenetic analysis of Paleozoic limbed vertebrates - Marjanović,David; Laurin,Michel (PeerJ Preprints, 2016)
The largest published data matrix for phylogenetic analysis of Paleozoic limbed vertebrates (Ruta M, Coates MI. 2007. Journal of Systematic Palaeontology 5:69–122) supported variously controversial hypotheses; e.g., it recovered Seymouriamorpha, Diadectomorpha and (in some trees) Caudata as paraphyletic and found the “temnospondyl hypothesis” on the origin of Lissamphibia (TH) to be more parsimonious than the “lepospondyl hypothesis” (LH) – though only, as we show, by one step. We report thousands of suboptimal scores due to typographic and similar errors and to questionable coding decisions: logically linked (redundant) characters, others with only one described state, even characters for which most taxa were scored after presumed relatives. Even continuous characters were unordered, the effects of ontogeny were not sufficiently taken into account, and data published after 2001 were mostly excluded. After these issues are improved – we document and justify all changes to the matrix –, but no characters are removed or added, we find (Analysis R1) much longer trees with e.g. monophyletic Caudata, Diadectomorpha and (in some trees) Seymouriamorpha; Ichthyostega rootward of Acanthostega; Anthracosauria rootward of Temnospondyli which includes Caerorhachis; the LH is 9 steps shorter than the TH (R2; constrained) and 12 steps shorter the “polyphyly hypothesis” (PH – R3; constrained). We then added 48 OTUs to the original 102. This destabilizes some parts of the tree, e.g. the positions of Anthracosauria, Temnospondyli and Caerorhachis. Yet, many added taxa have well-resolved positions, ranging from the well known Chroniosaurus (Chroniosuchia), which lies just crownward of Temnospondyli and Gephyrostegidae, to isolated lower jaws. Even though Gerobatrachus, Micropholis and Tungussogyrinus and the extremely peramorphic salamander Chelotriton are added, the difference between LH (R4) and TH (R5) rises to 12 steps, that between LH and PH (R6) to 17 steps; the TH also requires several more regains of lost bones than the LH. Brachydectes (Lysorophia) is not found next to Lissamphibia. We duplicated all analyses after coding losses of bones as irreversible. The impact on the results is modest. Anthracosauria is always rootward of Temnospondyli. With 102 OTUs, the LH (R7) is 10 steps shorter than the TH (R8) and 11 steps shorter than the PH (R9); with 150, the LH (R10) is 14 steps shorter than the TH (R12) – and 13 steps shorter than the PH (R11). Bootstrap values are mostly low, and plummet when taxa are added. Statistically, the TH (R2, R5, R8, R12) is not distinguishable from the LH or the PH, but the LH (R1, R4, R7, 53 R10) and the PH (R3, R6, R9, R11) may be distinguishable from each other under both taxon samples and both reversibility settings. A reliable test is not available. We discuss the relationships of certain taxa, approaches to coding, some character complexes, and prospects for further improvement of this matrix.
Keywords: phylogenetics; data matrix; morphology; Lissamphibia; Amphibia; Temnospondyli; Lepospondyli; Anthracosauria; reversal; phylogeny